(untitled) (American Journal of Financial Technology and Innovation, 2023)
In the recent decade, the surge in financial technology (fintech) has dramatically reshaped the financial landscape of many countries, including Nigeria. However, despite these developments, the economy continues to slide in a state of decline. The primary objective of this study was to investigate the impact of financial technology on Nigeria’s economic growth spanning 2012Q1 to 2022Q4. Using the Fully Modified Ordinary Least Squares (FMOLS) technique, the research focused on three aspects of fintech: Internet (Web) Transactions, Mobile Payment Transactions, and Instant Pay Transactions. The findings were enlightening. Web-based transactions showed a significant enhancement in Nigeria’s economic growth. These transactions not only simplified banking processes but also bolstered economic activities, making financial services more accessible to a wider demographic. In addition, Mobile Payment Transactions significantly impacted economic growth, acting as catalysts in spurring both urban and rural economic activities and inclusivity. On the other hand, Instant Pay Transactions displayed a rather unexpected negative impact on economic growth within the study period. While they augmented financial fluidity, they exhibited a negative, yet statistically significant, impact on overall economic growth. Drawing from these insights, specific recommendations were provided. For Web transactions, the paramount focus was suggested on fortifying the digital infrastructure and enhancing cybersecurity measures. This twofold approach would foster growth and shield the burgeoning digital economy from cyber threats. With their transformative essence, Mobile Transactions necessitated a dual strategy: expanding mobile connectivity, especially in underserved areas, and intensifying user education on safe mobile transactional practices. Given its negative relationship with economic growth, Instant Pay Transactions required a more proactive approach. An exhaustive infrastructure audit was advocated to expose any underlying inefficiencies. Simultaneously, a call for more stringent regulatory oversight on Instant Pay Transactions was made to align it more harmoniously with the nation’s broader economic objectives